Metode Waterfall dalam Pengembangan Sistem Inventaris Guna Meningkatkan Efisiensi Manajemen Stok Barang - Anis, Yunus; Wahyudi, Eko Nur; Kurniawan, Harnanda Cahya (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Mekarsari Minimarket was founded by the owner of the Al Asror Islamic boarding school with the aim of making it easier for Al-Asror Islamic boarding school students and local residents to get the goods they need. To be able to estimate the number of goods that must be provided to consumers, appropriate inventory data is needed for consideration. To obtain this data, an inventory information system is needed that suits your needs. In this research, an inventory information system for the Mekarsari minimarket was developed using the Waterfall method. The stages of the waterfall method are requirements analysis, system design, program writing, and program testing. Needs analysis was carried out by direct observation, interviews with minimarket owners and employees, and literature study. The system is designed based on the analysis results and displayed in the form of use cases and flowcharts. The system was created using the PHP, CSS programming language. The database used for the system is MySQL. After that the system was tested using the black box method. Having an inventory information system can help minimarket owners make the right business decisions based on available data.